1H/13C chemical shift calculations for biaryls: DFT approaches to geometry optimization. Issue 9 (29th September 2021) - Nguyen, Thien T.
Abstract : Twelve common density functional methods and seven basis sets for geometry optimization were evaluated on the accuracy of 1 H/ 13 C NMR chemical shift calculations for biaryls. For these functionals, 1 H shifts calculations for gas phase optimized geometries were significantly less accurate than those for in-solution optimized structures, while 13 C results were not strongly influenced by geometry optimization methods and solvent effects. B3LYP, B3PW91, mPW1PW91 and ω B97XD were the best-performing functionals with lowest errors; among seven basis sets, DGDZVP2 and 6-31G(d, p) outperformed the others. The combination of these functionals and basis sets resulted in high accuracy with CMAEmin = 0.0327 ppm (0.76%) and 0.888 ppm (0.58%) for 1 H and 13 C, respectively. The selected functionals and basis set were validated when consistently producing optimized structures with high accuracy results for 1 H and 13 C chemical shift calculations of two other biaryls. This study highly recommends the IEFPCM/B3LYP, B3PW91, mPW1PW91 or ω B97XD/DGDZVP2 or 6-31G(d, p) level of theory for the geometry optimization step, especially the solvent incorporation, which would lead to high accuracy 1 H/ 13 C calculation. This work would assist in the fully structural assignments of biaryls and provide insights into in-solution biaryl conformations.